Fonctions de production agricole au Québec - Archer, André (L'Actualité économique, 1979)
This study attempts to estimate the productivity of inputs to Quebec agriculture. It makes use of two Cobb-Douglas production functions: one aggregate, for Quebec as a whole, and the other regional, covering the farming regions 04 and 11, using 1976 data. From the results obtained, marginal productivities of inputs and returns to scale are determined and interpreted. The principal conclusions of this research are: while returns to scale are increasing for Quebec in general, they are constant for the regions 04 and 11. It ensues that, if there is no breakthrough in technology, there is no reason to change the scale of agricultural production in regions 04 and 11; the productivity of machinery is higher in Quebec than in the regions 04 and 11; livestock productivity is high everywhere; as for land and buildings and other inputs, their productivities are low in Quebec as well as in the farming regions 04 and 11. With respect to labor, its productivity is quite high in Quebec and in the regions 04 and 11. However, labor productivity in region 04 is superior to that in region 11.